Elicitation of asiatic acid in centella asiatica asiatica using kappaphycus alvarezii - Abdul Rahman Putra, Putri Nur Halimah (2016)
Centella asiatica is an endangered medicinal herb which used in the preparation of herbal drugs mainly due to the presence of four pentacyclic triterpene which are asiatic acid, asiaticoside, madecassic acid and madecassoside. It's over exploitation necessitates the development of conservation strategies and enhanced the production of secondary metabolites. In present study, the effect of various concentration of seaweed Kappaphycus alvarezii elicitor was used to increase the amount of asiatic acid production in C. asiatica. Four difference concentration of seaweed elicitor was treated in C. asiatica which are 0g/L, 2g/L, 4g/L and 8g/L. They are harvested at day 0, 7, 14 and 21 and soak with methanol to obtain crude brown extract. The amount of asiatic acid containing in the samples was analyzed by HPLC and area under the curve of retention peak was calculated by using a formula. The diameter of leaf, number of new shoots and flowers were measured during successive stages of development. In conclusion, K. alvarezii can increase the production amount of asiatic acid in C. asiatica at shorter time, which at day 14, concentration of 4g /L and 8g/L are the best while the additional of certain concentrations of seaweed elicitor can induce flowering in C. asiatica.